Fazlur Rahman Khan's understanding of tube structural system of skyscrapes - Md Nor, Khairul affendy; Shafie, Amir Akramin (IIUM Press, 2011)
The principal objective of this chapter is to discuss about contributions of Fazlur Rahman Khan, towards construction of skyscrapers. His innovations, namely frammed tube, trussed tube and bundled tube, had led to significant improvement on structural efficiency and made the construction of tall buildings economically viable. The chapter will also investigate on the improvement of structural system using Khan's innovation and its impacts on construction of current generation skyscrapers. Research methodologies used are book referencing, internet searching and journals referencing. Fazlur Rahman Khan was a structural engineer, renowned for his designs of structural systems in the second half of the 20th century, which then remain fundamental to all skyscrapers todate. He was born in 1929, in Dhaka, Bengal now Bangladesh.